ANALYSIS OF OBSOLESCENCE AND PRODUCTIVITY OF AUTHORS USING LOTKA LAW ON THE JOURNAL OF ENTREPRENEURSHIP IN 2015 – 2019 - Rhoni Rodin; Eka Apriyani (Publication Library and Information Science, 2021)
This research was conducted to determine the level of obsolescence of a literature and determine the author's productivity with the law of lotka in the literature on entrepreneurship in 2015-2019. The research method used is quantitative research methods by conducting citation analysis. In analyzing data, data is collected, submitted, processed and then presented in tables and graphs. The result of the research is the obsolescence level of the literature with an article entitled "The Effect of Organizational Citizenship Behavior on Performance with Service Quality, Satisfaction and Behavior Intention as Antecedents" with the obsolescence of literature and half-life of the last 17 years. And the shortest time for literature obsolescence is only 5 years, the article is entitled: "The Effect of Using Cooperative Learning Type Think-Pair-Share (Tps) on Entrepreneurship Learning Outcomes of Class X Students of Even Semester SMP Kartikatama 1 Metro T.P 2015/2016". Then for the calculation of authors who are often cited, namely I Ghozali, Singh, Sangeeta, Wafa, S.A and Suharti L. Each of the authors of the articles is the writer with the second rank on the subject of entrepreneurship. Most of the writers produce one article. The most productive writer produced 4 articles and got first place, namely Wiliams, then Muhammad Hassan and Berry L were in second place by producing 2 articles in the 2015-2019 period while the third rank was occupied by authors who produced 1 article in the 2015-2019 period, namely as many as 156 authors. Based on the test of Lotka's law on Entrepreneurship articles, it has an exponential value of (n) 3.7537, with the set (C) 0.9127 or 91.27%. From the graph it can be seen that there is a relationship between the number of authors and the number of articles produced as in the lotka law. The fewer the number of writers, the more articles are produced.